Giant alloyed hot injection shells enable ultralow optical gain threshold in colloidal quantum wells - Altintas, Yemliha (2020)
As an attractive materials system for high-performance optoelectronics, colloidal nanoplatelets (NPLs) benefit from atomic-level precision in thickness, minimizing emission inhomogeneous broadening. Much progress has been made to enhance their photoluminescence quantum yield (PLQY) and photostability. However, to date, layer-by-layer growth of shells at room temperature has resulted in defects that limit PLQY and thus curtail the performance of NPLs as an optical gain medium. Here, we introduce a hot-injection method growing giant alloyed shells using an approach that reduces core/shell lattice mismatch and suppresses Auger recombination. Near-unity PLQY is achieved with a narrow full-width-at-half-maximum (20 nm), accompanied by emission tunability (from 610 to 650 nm). The biexciton lifetime exceeds 1 ns, an order of magnitude longer than in conventional colloidal quantum dots (CQDs). Reduced Auger recombination enables record-low amplified spontaneous emission threshold of 2.4 μJ cm-2 under one-photon pumping. This is lower by a factor of 2.5 than the best previously reported value in nanocrystals (6 μJ cm-2 for CdSe/CdS NPLs). Here, we also report single-mode lasing operation with a 0.55 mJ cm-2 threshold under two-photoexcitation, which is also the best among nanocrystals (compared to 0.76 mJ cm-2 from CdSe/CdS CQDs in the Fabry-Pérot cavity). These findings indicate that hot-injection growth of thick alloyed shells makes ultrahigh performance NPLs.